2016
DOI: 10.1371/journal.pone.0153169
|View full text |Cite
|
Sign up to set email alerts
|

Xylazine Activates Adenosine Monophosphate-Activated Protein Kinase Pathway in the Central Nervous System of Rats

Abstract: Xylazine is a potent analgesic extensively used in veterinary and animal experimentation. Evidence exists that the analgesic effect can be inhibited using adenosine 5’-monophosphate activated protein kinase (AMPK) inhibitors. Considering this idea, the aim of this study was to investigate whether the AMPK signaling pathway is involved in the central analgesic mechanism of xylazine in the rat. Xylazine was administrated via the intraperitoneal route. Sprague-Dawley rats were sacrificed and the cerebral cortex, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 41 publications
1
10
0
Order By: Relevance
“…Administration of xylazine significantly decresased (P< 0.01) the pulse, respiratory rates and body temaperature. Significant decrease in pulse and not respiratory rates after pre-anaesthetic administration of alpha 2 -agoinst have been reported by other researchers in sheep (Mather et al, 2004) and in goats (Shi et al, 2016). Significant changes in the body temperature after xylazine administration in sheep have also been reported by others in sheep and in goats (Okwudili et al, 2014).…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…Administration of xylazine significantly decresased (P< 0.01) the pulse, respiratory rates and body temaperature. Significant decrease in pulse and not respiratory rates after pre-anaesthetic administration of alpha 2 -agoinst have been reported by other researchers in sheep (Mather et al, 2004) and in goats (Shi et al, 2016). Significant changes in the body temperature after xylazine administration in sheep have also been reported by others in sheep and in goats (Okwudili et al, 2014).…”
Section: Discussionsupporting
confidence: 60%
“…Xylazine hydrochloride is clinically used for sedative, analgesic and muscle relaxant properties during minor surgical and diagnostic procedures (Clarke and Hall, 1990). Xylazine is highly lipophilic nature and directly stimulates the central α2 adrenergic receptors and leads to a decrease in neurotransmission of norepinephrine and dopamine in the central nervous system (Shi et al, 2016). In veterinary anesthesia, it is a very common procedure of combination therapy and xylazine is often used in combination with ketamine because xylazine reduces the required dose of anaesthetic.…”
Section: Introductionmentioning
confidence: 99%
“…It is rapidly absorbed following intramuscular (i.m.) administration [ 36 , 37 ]. Xylazine is used in a variety of species including the rat and mouse [ 38 , 39 ] in conjunction with ketamine, to eliminate muscle rigidity [ 15 , 17 ].…”
Section: Resultsmentioning
confidence: 99%
“…The difference in the mRNA expression of AMPKα1 and AMPKα2 in the cerebellum and hippocampus indicated that the antagonists had no effect on AMPKα1 in these regions. One cause may be that the content in the brain of AMPKα2 is higher than that of the α1 subunit (28). Another reason may be that the nuclear localisation complex may also regulate gene expression when a stress response to ATP depletion occurs in the organism (29).…”
Section: Discussionmentioning
confidence: 99%